Gene expression analysis reveals genes related to heavy metals and produced water exposure in Synechococcus elongatus - Alaa Hassanien (19420603) (2025)
Produced water (PW), a major by-product of the petrochemical industry, contains a complex mixture of contaminants that limit its reuse and pose environmental risks if discharged untreated. Numerous treatment technologies have been developed to remediate this water, with bioremediation standing out as one of the most promising novel approaches. One such bioremediation method is through the application of cyanobacteria, which are able to remove pollutants such as heavy metals from produced water, although the mechanism by which the pollutants are removed is still unknown. In this study, a well-characterized cyanobacterium, Synechococcus elongatus, was used as a model organism to establish a proof of concept for identifying genes responsive to PW exposure and heavy metal stress. RNA sequencing was performed to analyze transcriptomic changes in S. elongatus grown in BG-11 (control) and exposed to 3 mg/mL of iron (heavy metal (HM)) or 25% v/v PW in BG-11. Differential expression analysis revealed that 11 and 67 genes were ≥ fivefold upregulated, and 337 and 27 genes were ≥ fivefold downregulated under HM and PW exposure, respectively, compared to the control. Among the over-expressed genes, the plasma membrane transporter, nitrate ABC transporter permease, was identified, suggesting its important role in the bioremediation process of heavy metals from wastewater. These findings provide foundational insights into stress-responsive gene networks in cyanobacteria and inform future bioengineering strategies for enhancing bioremediation capabilities in S. elongatus and related strains. Other Information Published in: International Microbiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10123-025-00715-x